PERTUMBUHAN DAN HASIL DUA VARIETAS KACANG HIJAU (Vigna radiata L.) PADA PEMBERIAN BERBAGAI DOSIS POC LIMBAH AIR TAHU - Ikram, Ikram; Faturrahman, Faturrahman; Madauna, Ichwan S (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2024)
This study aimed to determine the optimal dose of tofu wastewater-based organic fertilizer (LOF) on the growth and yields of two mung bean varieties, Vima 1 and Vima 3. The experiment was conducted at the Academic Garden of the Faculty of Agriculture, Tadulako University, Palu, from October 2021 to January 2022. A Randomized Block Design (RBD) with two factors was employed: mung bean variety (Vima 1 and Vima 3) and POC dose (0, 40 ml/plant, 50 ml/plant, 60 ml/plant, 70 ml/plant, and 80 ml/plant). The results indicated that both varieties showed similar vegetative growth responses to the LOF doses, with significant differences observed only in production components. The 80 ml/plant dose led to increased growth for both varieties, suggesting this as the optimal level for enhancing plant growth.